Financial Management Strategies for Business Actors as an Effort to Improve Performance and Competitiveness - Fauziyyah, Nurul; Ersyafdi, Ilham Ramadhan; Bestari, Ruli; Aryani, Habsyah Fitri; Ahmadi, Lusiana Putri; Prabowo, Muhammad Aras (Universitas Lambung Mangkurat, 2025)
Implementing this community service activity aims to answer the needs of MSMEs in the era of the global crisis known as COVID-19. This activity aims to provide practical knowledge and experience regarding financial management, implementing accounting, and other related matters, such as creating basic financial reports for MSMEs. The target participants of this activity are micro, small and medium enterprises, students, and the general public who want to increase their knowledge and insight regarding financial management strategies for business actors. The total number of participants who attended this agenda was 116 from various groups such as business people, professionals, students, and others. The method for implementing this activity is to use a PAR approach in the form of a national seminar through a virtual meeting which presents two resource persons from associations, practitioners and business actors so that they can provide various perspectives and knowledge that can provide future provisions for (potential) business actors. It is hoped that this activity can be a solution for business actors affected by COVID-19 or prospective business actors so that they become more alert and anticipatory in unpredictable economic conditions with high volatility.